Synthesis and photoelectric properties of an organic dye containing benzo[1,2-b：4,B-b＇]dithiophene for dye-sensitized solar cells - Gao, Yu-Rong; Chu, Ling-Ling; Guo, Wei; Ma, Ting-Li (Chinese chemical letters, 2013)
A novel benzodithiophene-containing organic dye BDT was synthesized and characterized as a sensitizer for a nanocrystalline TiO2-based dye-sensitized solar cell. Under simulated AM1.5G solar light (100mW/cm2) illumination, the DSC based on BDT gives a power conversion efficiency of 1.78%. A novel benzodithiophene-containing organic dye BDT was synthesized and characterized as a sensitizer for a nanocrystalline TiO2-based dye-sensitized solar cell. The BDT dye shows two major electronic absorptions. The absorption of the BDT dye covers a broad visible range from 300nm to 550nm. The benzodithiophene unit was used as a π bridge with several advantages: (1) It facilitates the electron transfer from the donor to the acceptor; (2) A facile structural modification on the 4,8-positions in the benzodithiophene unit can be achieved; (3) Fusing benzene with two flanking thiophene units improves the thermal stability. Under simulated AM1.5G solar light (100mW/cm2) illumination, the DSC based on BDT gives a power conversion efficiency of 1.78%.